The portable neutron generator designed for treatment of cancer - Dovbnya, A.N.; Tsymbal, V.A.; Stoyanov, A.F.; Shahov, D.Y.; Zaytsev, I.N. (Вопросы атомной науки и техники, 2016)
We propose the construction of portable neutron generator designed for some oncological decease (particularly – uterus cancer, rectum cancer) by influence of neutrons. We propose to use reaction of deuteron interaction with lithium or beryllium nuclei for production of neutrons. The compact deuteron accelerator design is developed, we estimated neutron output for possible targets, the design of stand for testing and adjustment of installation is proposed.